Pentadbiran tentera Jepun dan Thai di Terengganu 1942-1945 - Abdullah Zakaria Ghazali (Penerbit Universiti Malaya, 1996)
History of Japanese and Thai administration during the Japanese occupation in Terengganu, Malaysia, 1942-1945.